ELEMENT RESEQUENCING FOR USE WITH A MULTIPLE FRONT ALGORITHM - SCOTT, J. A. (International journal for numerical methods in engineering, 1996)
The multiple front algorithm is an extension of the frontal method to allow parallelism to be exploited in the solution process. The finite‐element domain is partitioned into a number of subdomains and a frontal decomposition is performed on each subdomain separately. For a given partitioning of the domain, the efficiency of the multiple front algorithm depends on the ordering of the elements within each subdomain. We look at the limitations of existing element reordering algorithms when applied to a subdomain and consider how these limitations may be overcome. Extensive numerical experiments are performed on a range of practical problems and, on the basis of the results, we propose a new element resequencing algorithm for use with a multiple front algorithm.